PowerPoint 2019 - Ashby, Deborah ([Packt Publishing], 2019)
"Microsoft PowerPoint remains one of the most popular business tools, and rightly so. A great PowerPoint presentation can be the difference between a sale won or lost, a successful or failed investment, and a new initiative launched or sidelined. Microsoft PowerPoint includes many tools and features to help in all these scenarios, yet so few people make full use of this amazing tool. You don't need to be one of them. In this in-depth PowerPoint 2019 course from Simon Sez IT, not only do we walk you through the most business-relevant PowerPoint techniques, you then get to put into practice what you've learned through exercises at the end of each chapter."--Resource description page